MANAGEMENT OF GRAHANI ROGA WITH TAKRA AND ASHVAGOLA: A REVIEW (International Journal of Ayurveda and Pharma Research, 2017)
Diseases emanating from GIT form a considerable part of medical practice in India and abroad. Starting from ancient time to the modern era, Grahani Dosha has remained a fore runner but has also behaved like the fountain head of many GIT ailments. The faulty lifestyle, wrong food habits and busy schedules with abnormal-stressed lifestyle, changed eating habits and their patterns, inadequate sleep and non-observance of daily regime, seasonal regime, night regime and Sadvritta are the reasons for growing metabolic diseases in society. Due to improper digestion of food, there is vitiation of the Dosha and Agni and symptoms like alternate Constipation and Diarrhoea, with associated symptoms are seen, which can be collectively called as Grahani Roga. All the renowned physician of Ayurveda has given an account of treatment modalities for Grahani Roga. Among the different food habits and medicinal preparations, Takrasevan and Ashvabgola have been taken in this study. Takra having Ushna Veerya, Kashaya Rasa, Madhura Vipaka & Ruksha Guna pacifies Vata, Pitta, potentiates the Agni and digests as well as absorbs the food articles, and Ashvagola having Madhura Rasa, Sheeta Veerya and Madhura Vipaka is Vata Pittashamak and give bulk to the stool, relieving the symptoms and treating the disease in a generous way. This study is an attempt of the author to explain the effect of Butter milk and Ashvagola in Grahanidosha with the help of Ayurvedic Pharmaco-dynamics and other experimental studies.